Influence of maternal anxiety on child anxiety during dental care: cross-sectional study - Busato,Paloma (2017)
ABSTRACT CONTEXT AND OBJECTIVES: Anxiety is usually classified as a disorder of neurotic nature and is often related to contexts of stress, which may include worries, motor tension and autonomic hyperactivity. The aim of this study was to assess the influence of mothers’ anxiety on their children’s anxiety during dental care. DESIGN AND SETTING: Analytical cross-sectional study conducted at in a private dentistry school in the south of Brazil. METHODS: Convenience sampling was used. All mothers of children undergoing treatment were invited to participate in this study. Data to investigate anxiety related to dental treatment among the children were collected through applying the Venham Picture Test (VPT) scale. For the mothers, the Corah scale was applied. A self-administered sociodemographic questionnaire with questions about demographic, behavioral, oral health and dental service variables was also used. RESULTS: 40 mother-child pairs were included in the study. The results showed that 40% of the children were anxious and 60% of the mothers were slightly anxious. Local anesthesia was the procedure that caused most anxiety among the mothers, making them somewhat uncomfortable and anxious (60%). Family income higher than R$ 1,577.00 had an influence on maternal anxiety (75.6%). Maternal anxiety had an influence on child anxiety (81.3%). CONCLUSION: Most of the children showed the presence of anxiety, which ranged from fear of dental care to panic, inferring that maternal anxiety has an influence on children’s anxiety. Dental procedures did not interfere with the mothers’ anxiety, but caused positive feelings, whereas they affected the children more.